The Relationship of Knowledge and Attitudes Towards Behavior of Personal Hygiene among Food Traders - Azzahra Sarah Fatimah Ramadhanti; Erny Kusdiyah; Tia Wida Ekaputri; Armaidi Darmawan; Citra Maharani (Journal of Medical Studies, 2025)
ABSTRACT Background: In Indonesia, inadequate hygiene practices often threaten food safety. This research aims to analyze the relationship between knowledge and attitudes of food traders towards their hygiene behavior. Methods: This research is an observational quantitative study with a cross-sectional approach conducted in June 2024 at Car Free Day Telanaipura, Jambi City. The research sampling technique used a total sampling method on 100 food traders. Data was collected through a questionnaire that assessed demographic profiles, knowledge, attitudes, and personal hygiene behavior and analyzed using the chi-square test. Results: The results show that 60% of respondents have good knowledge, while 42% have a good attitude regarding personal hygiene. Statistical tests show a significant relationship between knowledge of personal hygiene behavior (p=0.047) and a significant relationship between attitudes towards the personal hygiene behavior of traders (p=0.028). Conclusion: Good knowledge and attitudes towards personal hygiene are associated with better hygiene behavior among traders. Therefore, increasing hygiene knowledge and attitudes among food traders needs to be strengthened through ongoing education and outreach to improve food hygiene standards in public areas. Keywords: Personal Hygiene; Food Traders; Knowledge; Attitudes; Behavior